2022
DOI: 10.1021/acscatal.2c00216
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Mild Metal-Free Reduction of Epoxides to Primary Alcohols Mediated by HFIP

Abstract: The reduction of epoxides is a powerful tool to access anti-Markovnikov alcohols, but reported methods are poorly compatible with strongly electronically deactivated substrates. Here, we describe a general method for the linear-selective reduction of styryl oxides incorporating strong electron-withdrawing groups. The method remains compatible with more traditional epoxide motifs, such as aliphatic and electron-rich styrene oxides. Other (hetero)cycles such as oxetanes, tetrahydrofurans, aziridines and cyclopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…We then explored post-functionalization pathways. First, driven by the serendipitous formation of 2au and our recent study on the reduction of epoxides in HFIP, 4 the reductive ring-opening of isochroman 2e ring was achieved, using triethylsilane in HFIP in the presence of TfOH (Scheme 5A). The resulting alcohol 4a was obtained in 74% yield and further reacted with mesitylene to afford Friedel–Crafts product 4b in 91% yield, again using HFIP and TfOH at 80 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then explored post-functionalization pathways. First, driven by the serendipitous formation of 2au and our recent study on the reduction of epoxides in HFIP, 4 the reductive ring-opening of isochroman 2e ring was achieved, using triethylsilane in HFIP in the presence of TfOH (Scheme 5A). The resulting alcohol 4a was obtained in 74% yield and further reacted with mesitylene to afford Friedel–Crafts product 4b in 91% yield, again using HFIP and TfOH at 80 °C.…”
Section: Resultsmentioning
confidence: 99%
“…During our recent work on epoxide reduction using hexafluoroisopropanol (HFIP), 2 we found that the mechanism involved an initial Meinwald rearrangement, 3 in which epoxides were first converted in situ into the corresponding aldehydes before reacting further. 4 This observation triggered our interest, as aldehydes, particularly the aliphatic ones that are enolizable, are notoriously prone to side-reactions such as self-condensation, which render them unstable and difficult to store in pure form. As a result, some commercially available aldehyde derivatives are expensive and must be freshly purified before use.…”
Section: Introductionmentioning
confidence: 99%
“…A range of conditions was then explored in an effort to effect the efficient 7‐ endo ‐tet cyclization of compound 30 into isomer 8 [4b,10] but inevitably if this was formed at all then it was accompanied by significant quantities of the 6‐ exo ‐tet product 31 or the isomeric and related compounds 32 — 35 as shown in Figure 4. After considerable experimentation (Table 1), and by following a protocol for reductive epoxide ring‐cleavage reported by Leboeuf, [ 11 ] when substrate 30 was treated with methanesulfonic acid and triethylsilane in hexafluoroisopropyl alcohol (HFIPA) at ambient temperatures for 12 h then, as shown in Entry 11, Table 1 and Scheme 5, a 1 : 1 and chromatographically separable mixture of two major products, namely compounds 8 and 31 (26% yield of each), was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the need to develop an atom economic process under environmentally benign conditions is considered one of the primary focus of research in this field 3 . Recent developments in FC reaction focuses on using other electrophiles such as epoxides [4][5] , benzyl alcohols [6][7][8][9][10] & their derivatives 11 , benzyl fluorides 12 , aldehydes and ketones etc [13][14][15][16][17][18] . For example, in a seminal work by Hall and coworkers a ferrocenium boronic acid catalyst was developed for the FC arylation of deactivated benzylic alcohols 6 .…”
mentioning
confidence: 99%